On the genus of free loop fibrations over F0-spaces - Toshihiro Yamaguchi (International Journal of Mathematics and Mathematical Sciences)
We give a lower bound of the genus of the fibration of free loops on an elliptic space whose rational cohomology is concentrated in even degrees.